The effect of music preferences on 2.4km time trial and rating of perceived exertion among UiTM Pahang male sport science students / Ahmad Waqi Wizi - Wizi, Ahmad Waqi (Faculty of Sports Science And Recreation, 2019)
This study was set up in order to identify the effect of music preferences on performance time in a 2.4 km running time trial and also how music preferences would have significant effect on rating of perceived exertion during 2.4 km time trial. Thirty male participants aged between 18 to 19 years old of University Teknologi Mara sport science undergraduate student participated in this study. Participant runs two sessions of 2.4 km running time trial. This study uses one group pretest posttest design. The first was pretest session where participant completed 2.4 km time trial in no music condition. The second was posttest session where participant completed 2.4 km time trial with music preferences condition. The posttest session results were examined 5 days from the initial session. The result from this study indicated that each participant completed 2.4 km time trial faster in music preferences condition and also rated lower perception in rating of perceived exertion rather than no music condition. Listening to music preferences can actually improve time to completion in 2.4 km time trial as well as lowering perception of pain and distract an individual from the intensity of the task being performed during 2.4 km time trial.